Influence of communication exposure on women's beliefs and uptake of the safe motherhood program in Barangay Mintal, Davao City - Galacio, Jastene Angelene E.
This study determined the influence of communication exposure on mother?s beliefs and uptake of the safe motherhood program and identified the factors responsible for such influence. Using the one-shot survey design, this study was conducted in Barangay Mintal, Davao City among 110 randomly selected mothers of childbearing age whom safe motherhood is a relevant issue. Respondents? exposure to information on safe motherhood messages ranged from none to moderate. However, most mothers reported high knowledge on safe motherhood, a huge portion of the respondents had a high favorable attitude towards performing safe motherhood, an extremely high perceived social pressure among their significant others in performing safe motherhood, and a high perceived behavioral control to perform safe motherhood, furthermore, using the Spearman?s rho, associations between variables were determined. Communication exposure did not have significant relationships with mother?s belief and uptake of the safe motherhood program, however, other variables revealed significant correlations with the uptake of the program. A negative significant correlation was observed with age and communication exposure, and a positive significant correlation between exposure and knowledge. Respondent?s attitude towards safe motherhood was also positively and significantly correlated with subjective norms and perceived behavioral control. Given that, communication exposure is reportedly low but partial and full uptake of the program was reported to be extremely high this may indicate that other factors have influenced their uptake and beliefs. Optimal scaling using categorical regression (CATREG) showed that intention, which is the highest predictor of uptake together with subjective norms, attitude, and knowledge predicted the likelihood of uptake of the safe motherhood program. Moreover, most of the Theory of Planned Behavior (TPB) constructs presented significant associations in consistent with the postulate of the TPB. In addition, using chi-square test of independence significant relationship was also observed between monthly income and perceived behavioral control, civil status, attitude and subjective norms, family size and knowledge, education, and attitude, subjective norms, intention and uptake.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Speech/Corporate Communication